2013
DOI: 10.5539/ijel.v3n3p66
|View full text |Cite
|
Sign up to set email alerts
|

Innovating Instruction of Malay Grammar through a Word List Program

Abstract: The dilemma of teaching and/or learning grammar in a language that is often considered 'dry' and dull often happens not just to students, but also to teachers. One of the factors that contribute to this problem is the lack of appeal that could intrigue students to learn, understand and gradually master the grammar of a language. Consequently, the teaching and learning of grammar which ought to be "alive" will become irrelevant, namely to the new generation of IT literate students. Thus, this study attempts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The total data was 1473 posts of style themes (Colman, 2009) with sub-theme namely; appearance (Griffiths et al, 2018), identity (Yang et al, 2022Zinn et al, 2022), and Narcissistic subtheme (Lyvers et al, 2022). In analyzing the data that have been classified based on the themes, subthemes, and spectrums, we utilized AntConc application to prove and interpret the lexical issues found in each theme (Isam, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The total data was 1473 posts of style themes (Colman, 2009) with sub-theme namely; appearance (Griffiths et al, 2018), identity (Yang et al, 2022Zinn et al, 2022), and Narcissistic subtheme (Lyvers et al, 2022). In analyzing the data that have been classified based on the themes, subthemes, and spectrums, we utilized AntConc application to prove and interpret the lexical issues found in each theme (Isam, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Technology can prove beneficial for resolving these challenges for the sake of increasing learners' exposure to the language (Al Ghafri, 2010, Khalil, 2018, Nutta, 2013, providing an innovative learning experience, (Isam, 2013, Khalil, 2018, facilitating the use of authentic materials (Miller & Wu, 2018, Nutta, 2013, and allowing for a considerable degree of practice (Wyatt, 1984).…”
Section: Difficulties In the Learning And Teaching Of Grammarmentioning
confidence: 99%
“…Despite the importance of grammar knowledge, second and foreign language learners continue to experience difficulties due to the tediousness of the acquisition process. This is primarily due to the use of conventional teaching methods, in which grammar is taught directly from textbooks (Al-Essa, 2018, Isam, 2013Khalil, 2018;Wyatt, 1984), with grammatical structures presented in meaningless and decontextualized forms isolated from their context of use (Khalil, 2018). It has also been reported that students encounter difficulties internalizing English grammatical rules, particularly due to the existence of exceptions and the inclusion of different spellings and endings 2.…”
Section: Introductionmentioning
confidence: 99%